Systematic review: the role of e-government and human resources management in corruption prevention in Indonesia - Halilul Khairi,; Suwandi,; Selvi Diana Meilinda, (Penerbit UKM, 2024)
This research addresses inconsistencies in studies on E-Government’s role in preventing corruption. Maximising the role of E-Government in preventing corruption requires additional approaches, notably Human Resources Management (HRM). This research uses the PRISMA Systematic Review to examine the role of E-Government and Human Resources Management in preventing corruption in Indonesia. This research reviews results from the past 10 years, analysing 530 metadata records condensed into 20 articles indexed by Scopus and Sinta. Research results indicate that E-Government can be a powerful tool for preventing corruption but requires context-specific application. Apart from that, E-Government is one of many tools for preventing corruption; it requires supporting approaches such as the supremacy of law, accountability, economics, internet distribution, and government transparency to help the role of E-Government in preventing corruption. Indonesia has not optimised E-Government implementation due to insufficient professionalism, authority abuses, and an inadequate transparent system. A human resources management approach is needed to maximise E-Government and prevent corruption. Recommendations for further research adding other literature from the Web of Science (WoS) journal to enrich the literature and conducting quantitative testing involving large populations and samples as well as other approaches and variables in various regions in Indonesia can help confirm the role of E-Government and HRM in preventing corruption.